(untitled) (Nordic Journal of African Studies, 2003)
Language policies and planning in Nigeria have hitherto not been realistically responsive to the linguistic diversity in the country. Rather, they have succeeded in accentuating ethnic conciousness and vitality with language as a symbol. For example, Nigeria is now polarized along two linguistic lines – linguistic majority and linguistic minority. Our standpoint in this paper is that a situation such as this is inimical to our emerging democracy and our aspiration for national development. The paper, therefore, will examine language policy and planning attempts in Nigeria since independence to the present. Against the backdrop of a case study of language planning in a country like Canada, with similar linguistic problems, this paper advocates a government’s strategy of governance that allows for a greater decentralization of power, and that, which will recognize and protect the linguistic rights of all Nigerians.